Validity of Digital-Based COVID-19 Preventive Supplement Book to Empower Scientific Literacy and Critical Thinking Skills of Senior High School Students - Rhavy Ferdyan; Fitri Arsih; Muhyiatul Fadilah; Dwi Hilda Putri; Abdul Razak (International Journal on Integrated Education, 2022)
The development of learning materials such as digital-based supplement books needs to be done regarding the lack of integration of COVID-19 in biology subjects. Students need to dig up information about COVID-19 through scientific literacy and solve problems through critical thinking. Data collection techniques in this study consisted of a questionnaire. From the data collection, the instruments needed in this study include validation sheets by experts. The data were analyzed quantitatively to determine the category of validity and deepened with a qualitative analysis of the strengths and weaknesses of the book. Based on the results of validation by validators or experts, the COVID-19 preventive supplement book is generally very valid with the average validation score of the four validators being 93.8. The feasibility of the material is also determined by its quality. The material contained in the supplement book must also be adapted to current scientific developments, of course, related to COVID-19. The book developed is predicted to be very useful and supportive in learning biology, especially relevant materials such as material on viruses, the respiratory system, and the immune system. The feasibility of the book has been supported from the aspect of appearance, content, and language which was revised in such a way after validation.